2004
DOI: 10.1207/s15326942dn2503_6
|View full text |Cite
|
Sign up to set email alerts
|

Development of Response-Monitoring ERPs in 7- to 25-Year-Olds

Abstract: In a target discrimination task, trials with incorrect responses elicit event-related potentials (ERPs) that include an error-related negativity (ERN or Ne) and a later error-positivity (Pe). Substantial evidence points to the anterior cingulate cortex as the source generator of the ERN. We examined the development of ERP component morphology, amplitude and latency to processing of correct and incorrect responses in 124 children, 7 to 18 years of age, and 27 adults, 19 through 25 years of age. The ERN and Pe w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

70
364
17
2

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 304 publications
(460 citation statements)
references
References 55 publications
(68 reference statements)
70
364
17
2
Order By: Relevance
“…Pre-SMA/ACC is thought to be sensitive to conflict and the need for a behavioral change (in the form of presentation of negative feedback) and exhibits a mature pattern of feedback response by age 11-13. These findings are consistent with previous studies, which have demonstrated developmental changes between 8 and 12 years in error-related event-related potentials, which are thought to originate from pre-SMA/ACC (Miltner et al, 1997;Davies et al, 2004).…”
Section: Discussionsupporting
confidence: 93%
“…Pre-SMA/ACC is thought to be sensitive to conflict and the need for a behavioral change (in the form of presentation of negative feedback) and exhibits a mature pattern of feedback response by age 11-13. These findings are consistent with previous studies, which have demonstrated developmental changes between 8 and 12 years in error-related event-related potentials, which are thought to originate from pre-SMA/ACC (Miltner et al, 1997;Davies et al, 2004).…”
Section: Discussionsupporting
confidence: 93%
“…Both the 5-and 6-year-olds were required to respond within 1,300 msec of the target presentation. The 4-yearolds were required to respond within 2,000 msec, in line with the findings of developmental response literature (Davies et al, 2004;Hale, 1990;Kail, 1986Kail, , 1993. Following response execution or lapse of the response window, feedback was presented on the screen as either a 1-in.…”
Section: Methodsmentioning
confidence: 97%
“…Individuals who find an incorrect response more personally salient exhibit more controlled and slower responses after commission of an error (Davies, Segalowitz, & Gavin, 2004;Henderson, 2003;Luu, Collins, & Tucker, 2000). Response control reflects individual differences in overall performance strategy by assessing the degree of control or impulsivity evident in participants' RTs for correct and incorrect trials (Pailing, Segalowitz, Dywan, & Davies, 2002).…”
mentioning
confidence: 99%
“…[181][182][183][184][185][186] For example, there is evidence indicating important developmental changes during adolescence in neural systems involved in reward processing, 187 response inhibition in the context of emotional stimuli, 188 response conflict monitoring [189][190][191] and risk taking. 192,193 The impact of puberty upon the development of neural systems of emotion regulation remains to be fully examined.…”
Section: Adult Bipolar Disordermentioning
confidence: 99%